Evaluation of Genotoxicity and 28-day Oral Dose Toxicity on Freeze-dried Powder of Tenebrio molitor Larvae (Yellow Mealworm) - Han, So-Ri (The Korean Society Of Toxicology, 2014)
The larval form of Tenebrio molitor (T. molitor) has been eaten in many countries and provides benefits as a new food source of protein for humans. However, no information exists regarding its safety for humans. The objective of the present study was to evaluate the genotoxicity and repeated dose oral toxicity of the freeze-dried powder of T. molitor larvae. The genotoxic potential was evaluated by a standard battery testing: bacterial reverse mutation test, in vitro chromosome aberration test, and in vivo micronucleus test. To assess the repeated dose toxicity, the powder was administered once daily by oral gavage to Sprague-Dawley (SD) rats at dose levels of 0, 300, 1000 and 3000 mg/kg/day for 28 days. The parameters which were applied to the study were mortality, clinical signs, body and organ weights, food consumption, ophthalmology, urinalysis, hematology, serum chemistry, gross findings and histopathologic examination. The freezedried powder of T. molitor larvae was not mutagenic or clastogenic based on results of in vitro and in vivo genotoxicity assays. Furthermore, no treatment-related changes or findings were observed in any parameters in rats after 28 days oral administration. In conclusion, the freeze-dried powder of T. molitor larvae was considered to be non-genotoxic and the NOAEL (No Observed Adverse Effect Level) was determined to be 3000 mg/kg/day in both sexes of SD rats under our experimental conditions.